Keefektifan Metode Fitoremidiasi dengan Pemanfaatan Tanaman Eceng Gondok untuk Menurunkan Kadar Amoniak Limbah Rumah Sakit PKU Muhammadiyah Surakarta - Asela, Endar, H. Heru Subaris K., S.KM, M.Kes, Dwi Astuti SKM. M.Kes (2016)
Liquid waste containing ammonia subtances can affect human health and the enviroment. Ammonia levels based on preliminary test result will be undertaken at the Hospital of PKU Muhammadiyah Surakarta of 0,620 mg / l, the result exceeded the water quality standar of waste. One of the ways that can be done to reduce levels of ammonia with fitoremidiasi method using the water hyacinth plant. This research study design was a true experiment with pretes and posttest with control grup. Location of researc at the Hospital of PKU Muhammadiyah Surakarta. Phytoremidiation uses 4 plants, 6 plants, and 8 plants hyacint done for 7 days in 15 liters of waste water. The average yield of the activity level of ammonia after the treatments is 99.459%, 99.524%, and 99,606%. The statistical test used is the One Way Anova. The result of the study obtained plants water hyacinth effectiveto reduce the ammonia on the water waste debgab doses effevtie 8 plant (p-value 0,001).